Edukasi Kesehatan Mental dalam Meningkatkan Pengetahuan Remaja di SMAN 8 Marod - Darlis, Idhar; T.A, Tenri Diah; Putri, Adhinda; Kas, Sri Reskiani; Yanti, Putri; Ampang Allo, Asna; Mustakim, Musyahidah (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Adolescence is especially important for improving mental health because more than 50% of mental health problems begin at that time and many of them persist into adulthood. The increasing cases of adolescent mental disorders indicate a lack of effective mental health care for adolescents. This is clearly an important issue that has an impact on the mental development of teenagers. Addressing adolescent mental health is by increasing knowledge about the problem. The focus of this activity is to increase teenagers' knowledge about mental health and its impacts. The methods used in this activity are lectures and discussions. With a total of 60 teenagers participating, the education was carried out at SMAN 8 Maros. The results obtained after the education was carried out were an increase in the level of knowledge of teenagers regarding mental health and its impacts and how to deal with it. Advice to teenagers is expected to disseminate the information that has been obtained to other teenagers.